The Colegio del Cercado de Lima at the time of the expulsion of the Jesuits - Millar Carvacho, René (2021)
The expulsion of the Jesuits from the domains of the Spanish Crown, was followed by the preparation of inventories listing all the assets of each of the different schools and residences owned by the Order. Taking the inventory that was made of the Colegio del Cercado de Lima, we try to show the facilities it had at the time of the expulsion, the staff that occupied the premises, and the activities carried out by its members. We also analyze the temporary projection of certain aspects of the missionary function performed by the school. Finally, we review the patrimonial situation of this institution and its financial statement as of September 1767.